하수 2차처리 방류수의 총인 고효율 처리를 위한 응집·막분리 혼성처리 - 최욱진; 이병하; 박준홍; 차호영; 이병찬; 송경근 (대한상하수도학회, 2018)
This study investigated phosphorus removal from secondary treated effluent using coagulation-membrane separation hybrid treatment to satisfy strict regulation in wastewater treatment. The membrane separation process was used to remove suspended phosphorus particles after coagulation/settlement. Membrane separation with 0.2 μm pore size of micro filtration membrane could reduce phosphorus concentration to 0.02 mg P/L after coagulation with 1 mg Al/L dose of polyaluminum chloride (PACl). Regardless of coagulant, the residual concentration of phosphorus decreased as the dose increased from 1.5 to 3.5 mg Al/L, while the target concentration of 0.05 mg P/L or less was achieved at 2.5 mg Al/L for the aluminum sulfate (Alum) and 3.5 mg Al/L for PACl. Moreover, alum showed better membrane flux as make bigger particles than PACl. Alum showed a 40% of flux decrease at 2.5 mg Al/L dose, while PACl indicated a 50% decrease of membrane flux even with a higher dose of 3.5 mg Al/L. Thus, alum was more effective coagulant than PACl considering phosphorus removal and membrane flux as well as its dose. Consequently, the coagulation-membrane separation hybrid treatment could be mitigate regulation on phosphorus removal as unsettleable phosphorus particles were effectively removed by membrane after coagulation.